Intradural extramedullary cystic schwannoma of the cervical spine - Başaran Gündoğdu, Elif; Ekici, Mehmet Ali (The European Research Journal, 2019)
Giant cervical intradural extramedullary schwannoma with severe spinal cord compression is a rare entity. Tumor spread and size are very important for surgical approach. In this case, we report a 55-years-old male patient with a giant intradural-extramedullary cervical schwannoma extending between C5 and T1 and causing spinal cord compression that underwent total resection with laminoplasty at C5-6-7 levels. The patient developed no additional deficit. To preserve the cervical lordosis, the patient used a cervical collar for three months. There has been no recurrence during two years of follow-up. Using the appropriate surgical method is essential in patients with spinal tumor in order to avoid additional neurological deficits and achieve cure.